IRRI Rice Quality Assessment Kit commercialised and marketed globally - CGIAR Research Program on Rice (2019)
The IRRI Rice Quality Assessment Kit consists of a set of various tools that help measuring one or several paddy, milled rice or seed quality traits. Target users are trainers, extension workers, farmers groups, traders and millers. The quality kit was previously assembled and sold by IRRI but in 2019 was outsourced and is now sold by a private company (GrainPro Inc.).